Recycling Pictures as Attract Point to Youngster in Campus Program Promotion - Kartika Kusuma Wardani; Hertina Susandari; Anggra Ayu Rucitra; Arya Weny Anggraita (Jurnal Ilmu Komunikasi, 2018)
Educational institutions need promotion tools to attract their segmentation. Promotion medium is used to increase awareness so that the youngster know about information and are interested to register themselves. A medium that has ability to show campus program in short time both attract them is using video. Video is a combination of moving image, sound, visual effect and has complex process to reach best visualization. On the other hand, sometimes the institution only has collection of documentation in photography format. The problem is how to use photo documentation to become short attractive video that shows whole institution programs. Final execution to recycle collection of pictures is using parallax style. This creation of style changes the photos to be more lifelike, which move with three dimensional cinematic effect.